Exploring the psychological impact of the COVID-19 pandemic on PICU consultants, advanced nurse practitioners and trainee doctors. (2nd April 2022) - Christmas, Alex; Mackinnon, Catriona; Brincat, Edgar; Donnelly, Peter; Worrall, Mark
Abstract : Background: Paediatric intensive care unit (PICU) staff members are at risk of burnout, stress, and fatigue. The COVID-19 pandemic has affected how we live and work; we postulate this increases the risk of stress-related disorders. Aims: To explore the impact of the COVID-19 pandemic on the wellbeing of PICU clinicians. Methods: An anonymised, single-centre survey was sent to clinicians, comprising four sections: burnout, work-related stress, work-related fatigue, and work-life balance. Two free-text questions explored perceptions of work-life balance and measures to improve wellbeing. Results: 55.6% of respondents returned scores suggesting high burnout risk. 55.6% had answers suggesting work-related stress. 82.4% reported work-related fatigue. 55.5% felt that work-life balance had not improved during the pandemic. Conclusions: The proportion of staff at risk of burnout in this study is higher than that reported in pre-pandemic studies. Perceived work-life balance has been negatively impacted, and high levels of work-related stress and fatigue were identified.